Evidence of osteoarthritis disease modification with a Sn-117m microparticle device: a review and validation in mammalian models - Bendele, Alison; Doerr, Cynthia A.; Gonzales, Gilbert R.; Menardi, Robert; Schreiber, Eric; Stevenson, Nigel R. (Frontiers in Veterinary Science, 2025)
Osteoarthritis (OA) is a progressive joint disorder affecting mammals as well as many non-mammalian animals, characterized by cartilage degradation and synovial inflammation, yet current treatments focus solely on symptom relief rather than disease modification. Radiosynoviorthesis (RSO) using commercially available homogeneous Sn-117m microparticles (HTM) (Synovetin OA®, Exubrion Therapeutics, Inc.) injected into the arthritic joint space targets synovitis—a critical driver of OA progression—offering a novel therapeutic approach. This review collates preclinical and clinical evidence demonstrating HTM’s potential to alter OA’s natural course in mammals. We explore OA pathogenesis, emphasizing synovitis, macrophage activity, and the inflammatory cycle, alongside RSO’s historical use and Sn-117m’s mechanism: low-energy electrons targeting the inflamed synovium. Preclinical studies in male Lewis rats with meniscal tear-induced OA revealed reductions in synovial inflammation, cartilage damage, and osteophyte formation, suggesting a disease-modifying effect. Clinical trials in dogs with elbow OA further substantiate these findings: a Grade 1 & 2 OA study showed durable lameness improvement over 12 months—long after Sn-117m’s 13.9-day half-life (t½)—indicating benefits beyond the active irradiation period. A reinjection study found that 50% of dogs exhibited no OA progression on imaging, suggesting HTM’s capacity to slow disease advancement. Unlike NSAIDs, which relieve pain without addressing etiology, Sn-117m targets the source of inflammation. Corticosteroids are effective anti-inflammatories when delivered into the joint, but can cause thinning of cartilage, bone loss, and joint instability. This review substantiates Sn-117m RSO as a transformative veterinary therapy, bridging preclinical insights with clinical outcomes that strongly supports a positive disease-modifying mechanism.